2021
DOI: 10.1007/s10646-021-02480-9
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of phenotypic and genotypic resistance in the intestinal microbiota of rainbow trout (Oncorhynchus mykiss) exposed long-term to sub-inhibitory concentrations of sulfamethoxazole

Abstract: Emergence of phenotypic and genotypic resistance in the intestinal microbiota of rainbow trout (Oncorhynchus mykiss) exposed long-term to sub-inhibitory concentrations of sulfamethoxazole

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Although the concentration is much lower than the stricter MRLs for SAs in animal products required by China and the EU [ 9 , 10 ], their accumulation effects cannot be neglected. Some researchers have confirmed that antibiotics can enter the food chain through ingestion by aquatic organisms with exposure experiments [ 50 ]. Moreover, some antibiotics have also been widely detected in fish (without exposure experiments) that live in aquatic environments (ocean, river) in China [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the concentration is much lower than the stricter MRLs for SAs in animal products required by China and the EU [ 9 , 10 ], their accumulation effects cannot be neglected. Some researchers have confirmed that antibiotics can enter the food chain through ingestion by aquatic organisms with exposure experiments [ 50 ]. Moreover, some antibiotics have also been widely detected in fish (without exposure experiments) that live in aquatic environments (ocean, river) in China [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other factors could have been explored to further assess the vulnerability/tolerance of fish to chemical pollutants, such as individual sex, which was not tested in the present study (Petitjean et al, 2021), neurotoxicological markers (Beghin et al, 2021), DNA damage (Silva et al, 2021). Examination of alterations in the microbiota of exposed gudgeons could also be an interesting approach because the constant exposure to subinhibitory concentrations of antibiotics may induce dysbiosis (Labitt et al, 2021) and impact biotransformation efficiency (Tan et al, 2022). Other biological matrices (gills, livers, or plasma) or standardized species (Dreissenidae or Gammaridae) with better-known biotransformation rates could be considered.…”
Section: Toxicological Effects On Caged Fishmentioning
confidence: 99%
“…The term “sub-inhibitory”, which was originally described for pure cultures, is often applied to complex communities 16 20 . However, the members of a complex community differ in their response to antibiotics, with some members being inhibited and some members benefiting from the same antibiotic concentration 21 .…”
Section: Introductionmentioning
confidence: 99%